2014
DOI: 10.1002/ejsp.2054
|View full text |Cite
|
Sign up to set email alerts
|

The cost of forgiveness: Observers prefer victims who leave unfaithful romantic partners

Abstract: Ninety-six male fraternity members (Study 1), 112 female voters (Study 2), and 219 undergraduates (Study 3) read scenarios in which a group representative forgave, retaliated, or left a romantic partner after the partner's sexual infidelity was publically revealed. Observers rated a victim who forgave his or her partner to be as mature as a victim who ended the relationship, but also as weaker and less competent. They rated a victim who forgave to be more mature but almost as weak and incompetent as a victim w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Judgment of the victim's character. Three single-item measures were used to assess the extent to which participants felt that the victim was competent, mature, and strong, based on concepts measured by Smith et al (2014). The questions were set up to look like comments on a link to the story in social media.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Judgment of the victim's character. Three single-item measures were used to assess the extent to which participants felt that the victim was competent, mature, and strong, based on concepts measured by Smith et al (2014). The questions were set up to look like comments on a link to the story in social media.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from research on romantic relationships suggests that third parties’ perceptions of victims are affected by whether the victim forgives or not, and that the severity of the event matters. Smith et al (2014) found that third parties judged a victim as weaker and less competent if she forgave a romantic partner for committing a sexual infidelity than if she did not forgive him. Similarly, DiDonato and colleagues found that, although victims of more severe offences (i.e.…”
Section: Third-party Judgments Of Victims Who Forgivementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, future research can seek to discover more third-party responses to forgiveness or to forgivers. Past research has examined perceptions of forgivers along dimensions other than power, including morality (see Adams et al, 2015) and maturity (H. Smith, Goode, Balzarini, Ryan, & Georges, 2014). Researchers can empirically test whether these perceptions are influenced by the communicative components of forgiveness.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Moreover, previous research has documented various behavioral responses to forgivers, such as continued aggression (McNulty, 2011;McNulty & Russell, 2016), compliance (Kelln & Ellard, 1999;M. X. Zheng et al, 2018), and endorsement (H. Smith et al, 2014). It would be interesting to explore whether perceived forgiver power can facilitate positive reactions other than cooperation or can deter negative behaviors toward forgivers as well.…”
Section: Limitations and Future Researchmentioning
confidence: 99%